Effectiveness of Topical Steroids in Treating Herpes-Associated Erythema Multiforme and Review of Topical Steroids - Thongprasom, Kobkan; Sooampon, Sireerat (UI Scholars Hub, 2019)
50-year-old female presented at the Oral Medicine clinic at the Faculty of Dentistry, Chulalongkorn University, Bangkok with a chief complaint of severe pain in her oral cavity and lips for 1 week. She had no systemic diseases, except for vertigo, and was currently taking cetirizine hydrochloride. An oral examination revealed a hemorrhagic crust on her lips, scaly, large ulcerations on the upper labial mucosa, and multiple oral ulcerations on the right and left buccal mucosa. She had limited mouth opening and difficult in eating. She was treated with benzydamine hydrochloride mouthwash, triamcinolone acetonide 0.1% mouthwash, and fluocinolone acetonide 0.1% solution. The patient’s pain and severe oral lesions gradually reduced after treatment for one week. At the one month follow-up, all lesions had completely disappeared and the laboratory investigation report showed that she was Herpes simplex virus Ab IgG type I and Type II positive; therefore, the diagnosis in this case was Herpes associated erythema multiforme (HAEM). The aim of this case report is to show the effectiveness of various potent topical steroids in treating severe oral ulcerations without any side-effects. Potent topical steroids are recommended as an alternative treatment for severe oral ulcerations in HAEM patients.